Different Gestational Diabetes Phenotypes: Which Insulin Regimen Fits Better? - Mecacci, Federico; Lisi, Federica; Vannuccini, Silvia; Ottanelli, Serena; Rambaldi, Marianna Pina; Serena, Caterina; Simeone, Serena; Petraglia, Felice (Frontiers in Endocrinology, 2021)
Objective: Maternal characteristics and OGTT values of pregnancies complicated by gestational diabetes mellitus (GDM) were evaluated according to treatment strategies. The goal was to identify different maternal phenotypes in order to predict the appropriate treatment strategy. Methods: We conducted a retrospective study among 1974 pregnant women followed up for GDM in a tertiary referral hospital for high risk pregnancies (Careggi University Hospital, Florence, Italy) from 2013 to 2018. We compared nutritional therapy (NT) alone (n=962) versus NT and insulin analogues (n=1012) groups. Then, we focused on different insulin analogues groups: long acting (Det) (n=626), rapid acting (R) (n=100), both Det and R (n=286). We compared maternal characteristics of the three groups, detecting which factors may predict the use of rapid or long-acting insulin analogue alone versus combined therapy. Results: Among women included in the analysis, 51.3% of them needed insulin therapy for glycemic control: 61.8% Det, 28.3% combined Det and R and 9.9% R alone. Age >35 years, pre-pregnancy BMI >30, family history of diabetes, previous GDM, altered fasting plasma glucose (FPG), hypothyroidism and ART were identified as maternal variables significantly associated with the need of insulin therapy. Altered 1-hour and 2-hour glucose plasma glucose level at OGTT, age >35 years and previous GDM were found as independent predicting factors for the use of combined therapy with rapid and long acting analogues for glycemic control. On the contrary, pre-pregnancy BMI <25 and normal fasting plasma glucose values at OGTT were found to be significantly associated to the use of rapid insulin analogue only. Conclusion: A number of maternal and metabolic variables may be identified at the diagnosis of GDM, in order to identify different GDM phenotypes requiring a personalized treatment for glycemic control.